Towards a different vision of organizational politicization and its working mechanisms - marhoune, mhamed; balloum, ismahane (Journal of Social Sciences and Humanities, 2023)
Among the things that change in this research paper is the phenomenon of organizational politicization, as the reality of the situation predicts the increase in voices skeptical about the fact that organizations are managed rationally and rationally. Which it seeks to achieve, away from the goals and sustainability of the organization, which makes it dependent on a set of these behaviors emanating from social actors, they knew how to locate and articulate in all the parts of the organization, and this increases the widening of the behavioral gap between the reality of what individuals aspire to from the necessity of having a core affiliation to their organization, and what They find it in the reality of the situation that pushes them to act within a purely mechanical framework, so the work becomes a mere mechanism to secure their existence. Within such a bad organizational environment, phenomena such as organizational politicization, which are based primarily on a set of games and strategies, and a combination or combination of relationships that go beyond the controls, rules and procedures that govern the functioning of the organization, escalate and extend.